Pregnant People-Infant Linkage for Surveillance - Amro Hassan; Andrew Hamilton; Shelly Sital (International Journal of Population Data Science, 2024)
Objectives and Approach As maternal mortality and morbidity continue to progress, better data is needed to comprehensively understand the problem, especially in   underserved populations who are differentially impacted. Surveillance in safety-net populations is complicated by care fragmentation  and interoperability challenges between primary care and hospital settings. . AllianceChicago (AC), a health center-controlled network, supports a common data infrastructure across a set of Federally Qualified Health Centers (FQHCs) in Chicago that is further linked to a distributed query infrastructure connecting Chicago’s major health systems known as CAPriCORN.